Detection of Class 1 Integrons among Gram-negative Bacilli Isolated from Sputum Cultures of Patients with Lower Respiratory Tract Infections in Ahvaz, Iran - Mojtaba Moosavian; Mahtab Khoshkholgh Sima; Maryam Haddadzadeh Shoushtari; Mohammad amin Fazeli Naserabad (Pasteur Institute of Iran, 2018)
Introduction: Diffusion of antibiotic resistance genes by horizontal gene transfer has led to the fast emergence of multidrug resistance (MDR) among bacteria. Multiple classes of integrons are effective genetic elements which play a significant role in the acquisition and nosocomial dissemination of resistance factors in strains of Gram-negative bacteria, Pseudomonas aeruginosa, and Acinetobacter baumannii. Methods: In this study, 110 sputum samples were collected from hospitalized patients with tract infections. Identification of the isolates was performed by standard biochemical tests. The most frequent Gram-negative isolates were 25 Enterobacteriaceae (62.5%), (9 Enterobacter spp, 11 Citrobacter spp, and 5 Escherichia coli), 6 P. aeruginosa (15%) and 9 Acinetobacter spp (22.5%). Susceptibility of the isolates to antibiotics was carried out by Kirby-Bauer disk diffusion method according to CLSI guidelines, and finally, the class 1 integrons were detected by PCR. Results: Maximum resistance rate among Gram-negative isolates was observed to ceftazidime, co-trimoxazole, and cefotaxime with 89%, 87%, and 82%, respectively. A low-level resistance was recognized for imipenem 32% and gentamicin 34%, while an intermediate level resistance was found against the norfloxacin 40% and ciprofloxacin 44%. Out of 6 P. aeruginosa and 9 A.  baumannii isolates, 2 (33.3%) and 3 isolates (33.3%) were positive for class 1 Integrons, respectively, while all Enterobacteriaceae isolates (100%) were negative for class 1 Integrons. Class 1 integrons were detected among of MDR isolates. Conclusion: Our results showed that monitoring MDR isolates and detection of class 1 integrons in these isolates is necessary for promotion of antibacterial stewardship.